Identification of the eddy current method features in the implementation of computer simulation algorithms for controlling the characteristics of the food production equipment parts - Zashchepkina, N. M.; Zdorenko, V. G.; Sebko, V. V.; Markina, O. M. (World academy of materials and manufacturing engineering, 2019)
Purpose: The purpose of this article is to study the theoretical provisions of the operation of a vortex device in the implementation of a non-contact method of controlling the details of brewing equipment using computer simulation algorithms. Design/methodology/approach: The theoretical positions of thermal ECT operation with a copper product are obtained, which is controlled while maintaining a constant value of the magnetic field frequency f1 = 70.0 Hz, with small values of the generalized parameter x≤1.1 and increasing the parameter x due to the increase in the frequency of thermal ECT, that is, at x≥3.5. Findings: On the basis of computer simulation algorithms the results of the joint measuring control of diameter d, electrical resistance ρ and temperature t of the sample made of copper (in the temperature range from 20-160°C) and the results of determination of thermally dependent thermal ECT signals with the sample of equipment details and the values of specific normalized values that relate the ECT signals to the physical and mechanical characteristics of the samples of the equipment being monitored. Research limitations/implications: Product diameters range is 5 mm to 50 mm. The lower boundary is limited by the frequency of the magnetic field f = 20 Hz and the upper boundary by the diameter of the frame of the thermal eddy current transformer transducer is 50 mm. Perspective positions of work require further development in the direction of extending the limits of control of geometrical parameters of the samples due to the use of automated control systems based on overhead eddy current transformer transducers. Practical implications: The practical value of the work is to increase the overall likelihood of control of the parameters of brewing equipment parts by increasing its instrumental component Di, due to the reduction of measurement errors due to instrumental techniques and on the basis of computer modelling algorithms for three-parameter control of parts of brewing equipment, electrical and temperature parameters, allows to obtain the value of the overall control probability Dz = 0.998. Originality/value: The originality of the article is the study of the theoretical provisions of the eddy current transformer transducer and the implementation of a non-contact method of controlling the details of brewing equipment using computer simulation algorithms that take into account the modes of joint three-parameter control: at high values of the generalized parameter x (with three-parameter surface control), at small values of x (while controlling the value of the average cross section geometry, electrical, temperature settings) at a fixed frequency magnetic field (get information on the diameter d, resistivity ρ and temperature t with a certain depth of penetration of the magnetic field in the sample Δ).
Keywords: computer simulation; food production modernization; quantitative indicators; coefficients influence; errors of aggregate measurements